Perlindungan Hukum bagi Bank sebagai Pemegang Jaminan Hak Atas Tanah dan Bangunan Milik Debitur yang Disita oleh Komisi Pemberantasan Korupsi (KPK) - Abraarsyah, Abraarsyah; Sukarmi, Sukarmi (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to analyze legal protection for banks as holders of legal guarantees for land and buildings owned by debtors that were confiscated by the Corruption Eradication Commission (KPK). The research used juridical-normative type. The research used statute approach, conceptual approach, and case approach. This study used domain analysis techniques. The results showed that if the KPK confiscated the land and / or buildings of the debtor owner, the Bank, as the holder of the guarantee of the rights to the land and buildings, would receive legal protection both preventively and repressively.